The sacred and the secular : Bengal Muslim discourses, 1871-1977 - Murshid, Tazeen M. (Calcutta : Oxford University Press, 1995)
This study traces the emergence and development of a Muslim intelligentsia in Bengal and examines the tension between religious and secular perceptions which they experience in their social and political lives. It explores the various factors which have influenced the ideological position of the intelligentsia, such as ideas derived from their local Indian and trans-Indian linkages as well as contact with a colonial culture. It argues that while religion has always played an important role in the life of the intelligentsia its particular manifestation in political life is a recent phenomenon owing to colonial experiences as well as concerns about legitimacy in the post-colonial phase. It presents an in-depth account of the major discourses in nineteenth- and twentieth-century Bengal including controversies regarding language, identity and nationalism.
The distinctiveness of the study lies in its subject matter and the inter-disciplinary approach to it. The study has attempted to relate the ideological orientations of the intelligentsia to their social bases. It finds that the dominant ideology is determined to a large extent by the nature of the ruling elite, its social base as well as its educational and intellectual orientations.
Pt. I. 1871-1947. Ch. 1. The Emergence of a Muslim Intelligentsia in Bengal: Social Origins, Education and Employment. Ch. 2. Society and Culture: The Religious and Communal Questions. Ch. 3. Religion in Politics, 1937-1947 -- Pt. II. 1947-1977. Ch. 4. Growth and Development of the Intelligentsia in the Post-Partition Period. Ch. 5. Culture and Language: The Problem of Identity. Ch. 6. Faith, Authority and the Challenge of Secularism. Ch. 7. Religion, Religious Institutions and Social Norms.
Includes bibliographical references (p. [452]-483) and index.
Keywords: Intellectuals -- India -- West Bengal -- History; Intellectuals -- Bangladesh -- History; Muslims -- India -- West Bengal -- Intellectual life; Muslims -- Bangladesh -- Intellectual life; West Bengal (India) -- Intellectual life; Bangladesh -- Intellectual life